2012
DOI: 10.1021/jp3090183
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal Effects in Energy Absorption of Coupled Quantum Dot–Metal Nanoparticle Systems

Abstract: We theoretically study the optical properties of a hybrid nanostructure consisting of a metal nanoparticle and a semiconductor quantum dot. We derive a closed-form solution for the energy absorption spectra of the hybrid system and investigate the impact of the nonlocal dielectric response of a metal nanoparticle on the energy absorption. The results show significant modification when compared to those obtained with a local dielectric function. More specifically, the magnitude and shape of the energy absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 36 publications
1
48
0
Order By: Relevance
“…An Alkali atom can have γ q ∼ 10 7 Hz. The typical value for QD is about γ q ∼ 10 9 Hz [49]. In dye molecules, even though the radiative lifetime is as long as nanoseconds, the internal conversion rate (γ q ∼ 10 12 Hz) determines the duration of the excitation.…”
Section: Enhaced Duration For Plasmonic Oscillationsmentioning
confidence: 99%
See 1 more Smart Citation
“…An Alkali atom can have γ q ∼ 10 7 Hz. The typical value for QD is about γ q ∼ 10 9 Hz [49]. In dye molecules, even though the radiative lifetime is as long as nanoseconds, the internal conversion rate (γ q ∼ 10 12 Hz) determines the duration of the excitation.…”
Section: Enhaced Duration For Plasmonic Oscillationsmentioning
confidence: 99%
“…The localized electric field (five orders larger compared to the incident field [40]) interacts with the quantum emitter. Hence, a dipole-dipole type effective coupling occurs between the antenna and the quantum object [40][41][42][43][44][45][46][47][48][49]. Because of the coupling, a transparency window emerges at the center of the absorption spectrum of the antenna, see The plasmonic oscillations are driven by a harmonic force which stands for the incident light.…”
Section: Introductionmentioning
confidence: 99%
“…These values correspond to colloidal quantum dots (typically CdSe-based quantum dots) and have been used in various studies. 1,3,6,9,14,16,18,22,24,29 For e m ðxÞ, we use experimental values of gold. 49 We solve numerically, using a fourth-order Runge-Kutta method, Eqs.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…43 A structure that has attracted particular attention is a hybrid nanocrystal complex composed of a semiconductor quantum dot and a spherical metal nanoparticle. 1,[3][4][5][6][7][8][9][10][11][12][13][14][16][17][18][19][22][23][24][25][26][27][29][30][31][32]34 The optical response of this structure interacting with a weak probe field of varying frequency and a strong pump field of fixed frequency has already been considered in some works. 5,7,12,19,32 In particular, Lu and Zhu 7 investigated the probe absorption and dispersion of the probe field in the presence of the pump field and showed that a hole induced by coherent population oscillation appears at the absorption spectrum of the probe field when excitons and plasmons interact.…”
Section: Introductionmentioning
confidence: 99%
“…The excitonplasmon coupling can also induce Rabi oscillations [9][10][11], enhance second harmonic generation [12,13], generate bistability [14][15][16], etc. It can also alter for wave mixing and reverse the course of energy transfer between the QDs and MNPs [17,18].…”
mentioning
confidence: 99%